간호대학생의 학습성과 달성을 위한 지역사회간호학 실습운영 방안 - 양경희(Kyung Hee Yang), 최영애(Young Ae Choi), 박선욱(Seon Wook Park), 부윤정(Yun Jeong Boo), 송명희(Myeoung Hi Song) (한국간호연구학회지, 2020)
Purpose : This study was conducted to identify qualitative and efficient clinical practice operation plans by understanding and improving the operational conditions and difficulties of community health nursing practice courses. Methods : This study used a mixed research method that applied triangle design. The data of survey research were collected from 45 professors in charge of community health nursing at colleges and universities. In Focus Group Interview(FGI), 9 community health nurses participated for qualitative data collection. Results : The program learning outcomes linked to the community health nursing subject were the recognition of changes in health and medical policy at domestic and abroad, the integration of liberal knowledge and major knowledge, and the application of nursing process based on critical thinking in many universities. The core basic nursing skills related to the subjects were many in blood sugar measurement, vitality measurement and CPR. Difficulties in clinical practice were identified as appointment of the practical instructors, the selection of a clinical field educators, lack of communication with the university, non-payment of field instructor, and personal expenses of students. Conclusion : Administrative and financial support is needed for operational conditions of practice courses, and cooperation is necessary to increase the field adaptability after graduation. KCI Citation Count: 0